Savanna woody plants responses to mammalian herbivory and implications for management of livestock–wildlife landscape. Issue 3 (7th July 2021) - Kibet, Staline; Nyangito, Moses; MacOpiyo, Laban; Kenfack, David
Abstract: The need to address wildlife conservation outside of protected areas has become more urgent than ever before to meet environmental and socio‐economic goals. However, there is limited knowledge about how woody plants respond to herbivory within landscapes shared by wildlife and domestic herbivores in African savanna, thus management decisions might be based on inaccurate information and ultimately be ineffective. We compared woody vegetation dynamics between two adjacent ranches with different management objectives and subjected to varying levels of herbivory by both wildlife and domesticated mammals using 421 square plots of 400 m 2 nested on three transects, each 3 km long and purposively selected to minimize bio‐physical differences. Both species and structural diversity were significantly higher ( p < 0.05) in the site with lower levels of herbivory. Conversely, the site with higher levels of herbivory recorded enhanced biomass production for a selection of palatable forage species, perhaps due to compensatory re‐growth. This enhanced biomass however dampens as trees grow taller than the browsing zone. A higher intensity of herbivory seems to promote increases in browsing‐tolerant Acacia mellifera as well as homogenization of the vegetation architecture and lower structural diversity. Conversely, low intensity of browsing modified by environmental factors seems to promote proliferation of encroaching unpalatable species which are increasingly becoming a major rangeland management challenge in the study region. Managing landscapes for the co‐existence of both wildlife and livestock demands critical analysis of how vegetation responses to herbivory to ensure suitable ecological niches are maintained. To increase browse biomass for livestock within the landscape would demand that dominant palatable browse‐tolerant species are suppressed within the browsing zone of majority of browsing livestock kept by promoting appropriate browsing intensity. On the other hand, if the management objective is to promote co‐existence of both wildlife and livestock, then the strategy would be to promote structural diversity by varying livestock stocking rate. Given the movement of wildlife between properties, livestock stocking rates should be considered within a wider landscape than just individual private lands. Abstract : Over 65% of wildlife population in Kenya reside outside protected areas within communal and private lands. Community Wildlife and Private Conservancies are taking root in the country yet competing interests between conservation and livestock production are less understood. This study presents areas of compromise for sustainable livestock–wildlife landscape.